Kazakh and Arabic-Persian Vocabulary in Radlov's Turkic Dialects Dictionary: A Structural-Semantic Comparison - Malbakov, Myrzabergen; Kulmanov, Sarsenbay; Seitbekova, Ainur; Mamyrbek, Gulfar; Zhorabay, Temirlan; Seidamat, Assel; Mursal, Aikerim (Forum for Linguistic Studies, 2025)
V.V. Radlov's An Attempt at a Dictionary of Turkic Dialects is a monumental lexicographic source for the study of 19th-century Turkic languages, including Kazakh. This article investigates the structural-semantic characteristics of native Kazakh words and Arabic-Persian borrowings in Radlov's dictionary. The primary aim is to analyze how these lexemes were categorized,defined, and semantically represented, and to identify how their forms and meanings have evolved into modern usage. The methodology integrates structural linguistics, comparative-historical analysis, and statistical evaluation of lexical data. Lexical units were thematically classified (e.g., human, society, nature), and their grammatical, morphological, and semantic features were examined. Special focus was given to Arabic-Persian words, including their phonetic adaptation and degree of integration into the Kazakh lexical system. The findings show that many lexemes labeled by Radlov as archaisms or historicisms remain relevant in contemporary Kazakh, particularly in terminological or professional contexts. The study also reveals how certain loanwords acquired new meanings, underwent semantic shifts, or were reanalyzed through native suffixes. A linguostatistical analysis confirms the dominance of native Kazakh words in the dictionary corpus, while also highlighting the systematic treatment of loanwords. The research contributes to historical lexicography, Turkic studies, and the documentation of language contact phenomena, and offers a foundation for developing multilingual and diachronic dictionaries.